PISAAN SEBAGAI WADAH PENANAMAN MORAL DALAM ACARA INTAR TERANG MASYARAKAT PAKUAN RATU - Riah, Sanah; Zuhro, Syifa Athiyyatus (Program Studi Pendidikan Bahasa Lampung, FKIP Universitas Lampung, 2023)
Abstract This research study is used as a forum for instilling values ​​in society. The aim of the research entitled